2022
DOI: 10.35145/procuratio.v10i1.2014
|View full text |Cite
|
Sign up to set email alerts
|

The Pengaruh Kinerja Keuangan Perbankan Syariah Terhadap Produktivitas Umkm Dan Dampaknya Pada Pertumbuhan Ekonomi Indonesia

Abstract: Tujuan dari penelitian ini adalah untuk mengetahui pengaruh langsung dari kinerja bank syariah terhadap produktivitas UMKM dan terhadap pertumbuhan ekonomi, kemudian melihat pengaruh tidak langsung kinerja keuangan bank syariah pada pertumbuhan ekonomi melalui peran mediasi dari produktivtas UMKM. Metode penelitian yang digunakan adalah analisis jalur, dimana variabel independen kinerja keuangan bank syariah adalah CAR, ROE, NPF, FDR dan BOPO, variabel dependen adalah pertumbuhan ekonomi dan variabel interveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
1
0
1
Order By: Relevance
“…However, the amount of financing provided can pose a risk of increasing problem financing where the debtor is unable to fulfill his obligations in completing financing, when OE increases it will have an impact on NPF. The results of this study are in line with research conducted by Damanhur et al (2018) which states that OE does not affect NPF and Hellen et al ( 2019) that when OE is greater, the burden used for the formation of reserves in anticipation of losses due to non -return of funds channeled through financing will be diminishing and cannot cover the risk of channeling financing and contrary to the Siregar & Suryani (2022) research which stated that OE had a negative effect while Nengsih (2020) stated it was positive, while based on the research objectives it was known that the contribution of OE to NPF was 1.83%.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the amount of financing provided can pose a risk of increasing problem financing where the debtor is unable to fulfill his obligations in completing financing, when OE increases it will have an impact on NPF. The results of this study are in line with research conducted by Damanhur et al (2018) which states that OE does not affect NPF and Hellen et al ( 2019) that when OE is greater, the burden used for the formation of reserves in anticipation of losses due to non -return of funds channeled through financing will be diminishing and cannot cover the risk of channeling financing and contrary to the Siregar & Suryani (2022) research which stated that OE had a negative effect while Nengsih (2020) stated it was positive, while based on the research objectives it was known that the contribution of OE to NPF was 1.83%.…”
Section: Discussionsupporting
confidence: 90%
“…In the research conducted by Prastiwi (2021), The study discovered that NPF was significantly positively impacted by GDP, operating expenses, and operating income. Further investigation by Siregar & Suryani (2022) found that the Capital Adequacy Ratio (CAR), inflation, Return on Assets (ROA), and Financing to Deposit Ratio (FDR) did not significantly affect NPF in their study using data from the 2008-2014 timeframe. other studies carried out by Damanhur et al (2018) during the 2014-2015 period using the variables GDP, FDR, inflation, Bank Indonesia Sharia Certificates (SBIS), and total assets result found that partial inflation and SBIS have positive significance to NPF, while GDP has a negative significance to NPF.…”
Section: Inflasimentioning
confidence: 91%
“…Selain itu, penelitian oleh (Siregar & Suryani, 2022) menyoroti bahwa pembiayaan yang disalurkan oleh perbankan syariah dapat mendorong produktivitas UMKM dan berkontribusi pada pertumbuhan ekonomi Indonesia. Hal ini sejalan dengan temuan dari penelitian (Setiawan et al, 2022) yang menunjukkan peningkatan pembiayaan UMKM dari bank syariah juga dapat berdampak pada stabilitas moneter, meskipun perlu diwaspadai potensi kenaikan harga komoditas yang dapat memicu inflasi.…”
Section: Pendahuluanunclassified